Certain biochemical studies on the uterine flushings of normal and endometritis cows - RAVI KUMAR, B P; DEVRAJ, M; JAYAKUMAR, K (The Indian Journal of Animal Reproduction, 2007)
The biochemical parameters viz. pH, alkaline phosphatase (ALP) and total protein in the uterinetlushings of estrus cows with endometritis (n=72) and normal cows (n=l2) were studied. The ph,ALP and total protein in the uterine tlushings were higher (P
Keywords: Crossbred cows; Uterine flushing; pH; Alkaline Phosphatase; Total protein; Endometritis